Plugs - Steven Connor (University of Edinburgh, 2010)
Plugs are peculiarly intimate objects. Plugs are archaic things, that belong to an economy of spaces in which what mattered was to seal, to store, to quarantine and dam up flow. But now the plug is used for different purposes, to establish connections, and to draw together places and times. Plugs are scale-transformers: they used to keep proximal things distant, now they bring distant things up close. We use plugs not to keep things apart, but to become a part of them, to plug in rather than plug up. Plugs used to keep things in their place, enforcing a world governed by the prepositions ‘in’, ‘on’ or ‘at’. Now the plug is the enabler of relationships signified by prepositions like ‘through’, ‘across’ and ‘between’. As such, the plug is a prime example of the interference between spatio-temporal dispensations that is so much a feature of the modern world. Perhaps the plug is itself a connector between the archaic and the contemporary.